2020
DOI: 10.1177/0030222820918674
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Grief, Posttraumatic Stress, and Depression Among Bereaved Parents: Prevalence and Response to an Intervention Program

Abstract: Bereaved parents may experience diverse psychological symptoms. Possible interventions are not yet well established. In this study, the psychological symptoms of 323 bereaved parents (mean age = 39.97, SD = 7.21, 52.0% female), referred to a 4-week family-oriented rehabilitation (FOR) program, were assessed. The baseline assessments indicated that 160 (49.5%) parents showed symptoms of prolonged grief disorder (PGD). Complicated grief was indicated in 272 (84.2%), depression in 191 (59.1%), and posttraumatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…38 Depression is commonly reported among parents experiencing child loss. [9][10][11][12] In our study, mothers had greater symptoms of depression than fathers consistent with prior research on parental bereavement 9,10 and higher prevalence of major depressive episodes in women compared with men in the general U.S. population. 38 Greater symptoms of depression were also seen in parents of children that died at an older age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…38 Depression is commonly reported among parents experiencing child loss. [9][10][11][12] In our study, mothers had greater symptoms of depression than fathers consistent with prior research on parental bereavement 9,10 and higher prevalence of major depressive episodes in women compared with men in the general U.S. population. 38 Greater symptoms of depression were also seen in parents of children that died at an older age.…”
Section: Discussionsupporting
confidence: 90%
“…[16][17][18][19] Similar to prior work, bereaved parents in our study experienced substantial adverse mental health symptoms including symptoms of complicated grief, depression, and post-traumatic stress. 6,7,[9][10][11][12] Parents with stronger therapeutic alliances with PICU physi-cians demonstrated less symptoms of complicated grief during bereavement; however, therapeutic alliance was not significantly associated with lesser symptoms of depression, post-traumatic stress, or better overall health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Depression is commonly reported among bereaved parents. 9,32,33 We previously found that attachment insecurity, being a mother, and the death of an older child were independently associated with increased depression symptoms in our parent cohort 6 months after a child's death. 8 At 13 months, we found attachment-related anxiety continued to be independently associated with depression symptoms.…”
Section: Discussionmentioning
confidence: 68%
“…38 Attachment insecurity, being a mother, and sudden, unexpected death were independently associated with greater PTSD symptoms in our parent cohort 6 months after a child's death 8 consistent with other reports. 9,32,39,40 At 13 months, only parent education was independently associated with PTSD symptoms when adjusting for 6-month symptom scores. Parents with a high school education had significantly more PTSD symptoms than parents with a college degree or higher.…”
Section: Discussionmentioning
confidence: 97%